Factors that Influence Student Speaking Performance : (Study on Students Majoring in Accounting Faculty of Economics and Business UNMUH Jember) - Yayah Ikhda Nevia; Nurul Qomariyah; Iskandar Iskandar; Wardatul Hasanah; Nurul Hasanah; Rahman Rahman (Pusat riset dan Inovasi Nasional, 2025)
In an increasingly globalized job market, English-speaking proficiency has become an essential skill, particularly for non-English major students such as those in Accounting. This study aims to identify and analyze the factors influencing the speaking performance of students in the Accounting Department, Faculty of Economics and Business, Universitas Muhammadiyah Jember. Utilizing a quantitative approach and survey method, data were collected from 218 students selected through stratified random sampling. Instruments included questionnaires measuring language anxiety, self-efficacy, learning motivation, learning environment, and exposure to English, as well as an English-speaking test. The findings reveal that internal factors such as language anxiety, self-efficacy, and learning motivation significantly influence speaking performance. Meanwhile, external factors—learning environment and exposure to English—also contribute, albeit to a lesser extent. The results suggest the need for a holistic approach in improving students’ English-speaking abilities by addressing both psychological and environmental aspects of learning.